Proference: Behavioural Mix Between Propensity and Preference on Financial Market - Emil DINGA (European Journal of Interdisciplinary Studies)
The origin of economic preference is still disputable inside general economic theory and, especially, inside microeconomics (more specifically, regarding financial market functioning). The invariant vs. adjustable nature, or the objective vs. subjective character of the economic preference are within the core of conceptual, methodological, and instrumental debates and controversies. The paper enters this polemic with a new proposal, namely a model which builds, for the behaviour on financial market, the concept of propensity (coined by Karl Popper), from the objective/invariant side, and the concept of preference, as a behavioural mix which could be named as proference. To this end, the normative framework of society, viewed as a cultural geodesic will is aimed at to give the relative stability to the preference which, in turn, will act in an adaptive way on the cultural geodesic, in an evolutionary circular causality. Therefore, a new mechanism of financial market functioning – which could be named as Proference-Based Market Hypothesis (PBMH) – is proposed and (in its essential features) discussed. The main findings of the research are: a) although the economic preference is, generally, idiosincratic, however it is (necessarily) anchored to a quasi-objectified (not objective!) pillar, namely, to the cultural geodesic of the society as a whole; b) any economic preference is adaptive, and its adaptivity is so that it enters a co-evolution process with the cultural geodesic; c) in fact, on the financial market we always meet the preference, never we meet neither the propensity (that is, the cultural geodesic per se), nor the preference (that is, the idiosyncrasy per se); d) the concept of preference should be taken over by the financial theory and introduced into the logical and quantitative models of the financial market.